2020
DOI: 10.3855/jidc.13156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and laboratory characteristics of patients hospitalized with COVID-19: single centre report from Egypt

Abstract: Introduction: The recently discovered novel coronavirus disease (COVID-19) has emerged in Wuhan, China, since January 2020. Egypt reported a low incidence of infection when compared with other countries. The aim of the study was to assess the characterization of COVID-19 infection among the Egyptian population. Methodology: Data were collected from a single COVID-19 quarantine hospital in Cairo. A total number of 195 cases were included with their clinical, laboratory, and radiological data. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In our study population, there were 34 COVID-19 pregnant ladies (3.4%) which is much higher compared to a national reported rate of (0.286%) for females in the reproductive age[ 38 , 41 ]. This marked discrepancy can be explained by the societal concern over pregnancy with concerns over the mother and child and immediate request for medical advice.…”
Section: Discussionmentioning
confidence: 65%
“…In our study population, there were 34 COVID-19 pregnant ladies (3.4%) which is much higher compared to a national reported rate of (0.286%) for females in the reproductive age[ 38 , 41 ]. This marked discrepancy can be explained by the societal concern over pregnancy with concerns over the mother and child and immediate request for medical advice.…”
Section: Discussionmentioning
confidence: 65%
“…Studies from India have shown that up to 14% of symptomatic patients developed a severe illness and the in-hospital mortality ranged was 4.5 to 5% with similar risk factors as those reported from Bangladesh [5,6]. A Singlecenter study from Egypt reported a greater incidence of hospitalization and severity in patients with an age of greater than 50 years [7]. Limited data have been reported from small studies in Pakistan largely confined to intensive care settings [8,9].…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, variations were also noted between the second and third waves [14] , [15] . Despite the changes in patients’ demographic, clinical, and laboratory characteristics with COVID-19 during the different pandemic waves, only a few studies have observed these characteristics in Egypt during the first pandemic wave [4] , [16] . Furthermore, no previous studies were retrospectively conducted on patients with COVID-19 to determine these characteristics in Egypt during the second and third waves.…”
Section: Introductionmentioning
confidence: 99%